Awareness of general equilibrium effects and unemployment - Gersbach, Hans; Schniewind, Achim (Discussion paper series, 2001)
We examine wage-bargaining in a two-sector economy when employers and labor unions in each sector are not always aware of all general equilibrium feedback effects. We show analytically that if agents only consider labor demand effects, low real wages and low unemployment result. With an intermediate view, i.e. when partial equilibrium effects within a sector are taken into account, high real wages and unemployment result. If all general equilibrium effects are considered at once, low real wages and low unemployment again result. The assumption that unions and employers' federations are not able to incorporate all feedback effects from other sectors may explain the persistence of high unemployment in Europe.
Keywords: Graue Literatur; Arbeitspapier